Modified Predictive Control for a Class of Electro-Hydraulic Actuator - Abdulrahman A.A. Emhemed; Rosbi Bin Mamat; Ahmad ‘Athif Mohd Faudzi; Mohd Ridzuan Johary; Khairuddin Osman (Institute of Advanced Engineering and Science, 2016)
Many model predictive control (MPC) algorithms have been proposed in the literature depending on the conditionality of the system matrix and the tuning control parameters. A modified predictive control method is proposed in this paper. The modified predictive method is based on the control matrix formulation combined with optimized move suppression coefficient. Poor dynamics and high nonlinearities are parts of the difficulties in the control of the Electro-Hydraulic Actuator (EHA) functions, which make the proposed matrix an attractive solution. The developed controller is designed based on simulation model of a position control EHA to reduce the overshoot of the system and to achieve better and smoother tracking. The performance of the designed controller achieved quick response and accurate behavior of the tracking compared to the previous study.